Understanding The Teacher's Intention to Use Artificial Intelligence for Accounting Learning - Fachrurrozie, F; Nurkhin, Ahmad; Santoso, Jarot Tri Bowo; Astuti, Dwi Puji; Mukhibad, Hasan (Proceedings International Conference on Education Innovation and Social Science, 2024)
This research aims to analyze the factors that determine accounting teachers' intentions to use artificial intelligence in learning using the technology acceptance model (TAM) that has been developed. The research respondents were high school and vocational school accounting teachers in Semarang City, Central Java, Indonesia. 73 units of data were obtained using accidental sampling techniques. Questionnaires developed by previous researchers were used to obtain research data. SEM-PLS is used as a data analysis method. The research results indicate that only perceived usefulness can determine the level of teacher intention to utilize AI in learning. Other variables were not proven to have a significant influence. Some respondents thought that using AI was not an easy thing to do. Facilities and social support cannot encourage them to utilize AI in learning. Respondents also do not have sufficient IT competency, so they appear worried and less confident about utilizing AI in learning. The practical implication of this research is the importance of training and education for teachers so that they can utilize AI in learning because they are already convinced of the benefits of AI.